Relationship between the Consumer Price Index and the Producer Price Index for Six South American Countries - Cerquera Losada, Oscar Hernán; Murcia Arias, Juan Pablo; Conde Guzmán, Jonas (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper analyzes the relationship between the consumer price index and the producer price index for six South American countries Brazil, Colombia, Ecuador, Peru, Paraguay and Uruguay. To determine this relationship we estimated an autoregressive vector model or a model of error correction vectors, depending on the level of integration of the two variables for each country. In addition, the impulse response analysis was performed, and the Toda and Yamamoto causality test was developed. The periodicity of the data varies for each country, as it depends on the availability of the information. Three VAR models (Brazil, Peru and Uruguay) and three VEC models were applied (Colombia, Ecuador and Paraguay) the estimated VAR models, is that in the impulse response function, after a shock of the CPI and / or the PPI on the other variable and on itself, the effects disappear in time and the variables return to their original values. In the VEC model on the other hand, after a shock of the CPI and / or the PPI on the other variable and on itself, the effects do not disappear in time, and therefore the variables present permanent changes in the time.